Analisis Kelayakan Pembangunan Fasilitas Vulkanisir Ban Pesawat Terbang Di Indonesia Dan Strategi Pengembangannya: FEASIBILITY ANALYSIS OF DEVELOPMENT OF AIRCRAFT TIRE RETREADING FACILITIES IN INDONESIA AND ITS DEVELOPMENT STRATEGY - Franciscus, Freddy (Jurnal Teknologi Kedirgantaraan, 2021)
Airplane tire retreading is the process of reconditioning an airplane tire layer after several take- offs and landing times. Airplane tire retreading can be done between 3-5 times depending on the wear rate of the tire layers.The total number of aircraft operating in Indonesia is 1259 according to data from the DKPPU, and data from INACA 'Indonesia Aviation Outlook 2017' the number of Wide Body jets is 36 and Narrow Body is 414. From these data, the tires with the largest population and the same size is the aircraft tires B737-800/900/ER and A320-200/300 with the number of tires on the Nose Landing Gear/NLG are 806 EA and in the Main Landing Gear/MLG are 1612 EA. The available information states that the need for retreading tires for all Jet aircraft in Indonesia is around USD 13 million per year. About 80% or around USD 10.4 million per year is spending on retreading aircraft tires for B737-800/900/ER and A320- 200/300.This figure is a big opportunity for Indonesia MRO However, MRO (Maintenance Repair & Overhaul) Indonesia cannot take this opportunity because it still does not have the ability to retread airplane tires. For this reason, the authors conducted a feasibility analysis for the construction of aircraft tire retreading facilities for the B737-800/900/ER and A320-200/300 aircraft in Indonesia and conducted a strategic analysis necessary for the construction of the tire retreading facility to be successful. From the feasibility calculation, it is obtained 29.6% ROI (Return On Investment) and 4.8 year PBP (Pay Back Period) shows that the construction of the B737-800/900/ER and A320-200/300 aircraft tire retreading facilities is very feasible. Several strategies to achieve this are collaborating with Original Equipment Manufacturer/ OEM, seeking strategic partners, asking for support from the Government (the Ministry of Industry) by submitting the tire retreading facility development to the Aerospace Industry Roadmap.